DISAIN MONITORING DAN PENGENDALI BEBAN PADA PANEL LISTRIK BERBASIS IOT MENGGUNAKAN WEB SERVER - Aditya, Lukman; Prayitno, Hedy; Naibaho, Nurhabibah (Jurnal Kajian Teknik Elektro, 2025)
Electrical energy efficiency can be realized with monitored and controlled use. By adding that an internet of Things (IoT) based monitoring and control system on the electrical panel can be used to regulate electrical loads and monitor electrical energy usage in real time. In this research, a load monitoring and control system was designed using 4 load sharing channels, each with a 4 A MCB and a 10 A main line MCB. Each load channel is designed to have a capacity of 900 watts, and the total load for 4 channels is 2200 watts. The PZEM-004T module is used to read power consumption values, which is connected to the ESP32 to send data via WiFi internet which can be accessed via a browser on a PC or mobile device. The IoT-based control system allows users to select the load on the channel by selecting on or off on the browser display. There are four load channel options and one channel option to activate or deactivate all loads. Tests were carried out on the load channel using five 500 watts halogen lamps, obtained a maximum power of 1994.30 watts, a maximum current of 9.01 A and an average voltage of 226.56 Volts. Testing on one of the load channels obtained a maximum power of 841.50 watts, maximum current of 3.66 A. This test can be a reference for other load channels, because it has the same design characteristics